Pengaruh Penggunaan Magnesium Sulfate (MgSO4) saat Antenatal sebagai Neuroprotektor Bayi Prematur terhadap Perkembangan Motorik Kasar Usia 2-3 Tahun - sariati, yuseva; Nooryanto, Mukhamad; Anggraini, Putri Diah Ayu (Journal of Issues in Midwifery, 2017)
AbstractIndonesia is the country with the fifth highest figure in the world of prematurity. The incidence of severe preeclampsia in Indonesia as much as 31.04%.Indonesia still use magnesium sulfate as an anti-seizure medications and recurrent seizures. Some developed countries in the world have been using magnesium sulfate as a neuroprotective fetus during antenatal for baby with a risk of premature birth. Premature babies have an increased risk of morbidity short term and long term. Nearly 50% of premature babies have neurological problems such as motor disorders. This study aimed to determine the effect of a history of the use of magnesium sulfate in the mother during antenatal against gross motor development in children aged 2-3 years. Analytic observational research with cross-sectional approach. Samples were selected by using purposive sampling with 30 respondents. Collecting data on the data preterm infants with a history of giving antenatal magnesium sulfate obtained through medical record RSIA Puri Bunda Malang and gross  motor  development  is  obtained  by means of door-to-door using a checklist denver II. Analysis of the results  of  studies  using the  Fisher  Exact Test correlation test. The research data is obtained as much as 43.3% of respondents with a history of antenatal magnesium sulphate diagnosed normal gross motor development,  6.7%  suspect  and  no  diagnosed untestable. While the respondents without a history of antenatal magnesium sulphate showed 16.7% of children diagnosed normal gross motor development and 33.3% suspect and no respondents who were diagnosed untestable. The results showed that there was a significant effect (p value = 0.008), so that it can be concluded that a history of antenatal magnesium sulfate use in premature babies  have a better effect than the group that did not have a history of use of antenatal magnesiumsulfate.